Enhancing e-IDs authentication with NFC - Youssef, T.; Campos, A.; Guerreiro, A.; Coutinho, C. (Procedia Computer Science, 2024)
In the modern times, the heavy footprint of Information and Communication Technologies in the everyday life brings multiple challenges to the ordinary citizen, like having a digital profile on numerous services and institutions. The spread of authentication services that need to be verified to perform simple tasks is thus overwhelming. Many countries hence developed elaborated solutions to unify some of the authentication services around a single e-ID card to help performing different everyday tasks. The burden associated with carrying a smartcard reader to authenticate, or the time spent and complexity of the authentication using Mobile Digital Tokens represent an adversity for citizens who are not so digitally educated. NFC is a technology that is growing in usage every year and is widely adopted now. It is easy and fast to use. This paper proposes a safe, easy, and fast way to implement NFC-based authentication in an e-ID card and discusses its benefits.